DEVELOPING THE TECHNOPREUNARY SOUL FOR POSYANDU MEKARSARI KRAMATBARU WOMEN THROUGH THE DIGITALIZATION BUSINESS DEVELOPMENT PROGRAM TO ADD FAMILY INCOME - Yulaikah, Yulaikah; Azizi, Enji; Nurhikmat, Mira; Soraya, Ketty; Nurliana, Lia (LPPM Univ. Ibn Khaldun Bogor, 2023)
The economy in Indonesia is currently declining, due to a worldwide pandemic causing the Indonesian economy to experience a recession, as well as the global economy which is also experiencing a recession. Indonesia's economic growth was minus 5.32 percent in the second quarter of 2020. The figure had improved, although it was still in the minus category, namely 3.49 percent. The impact of this minus economic growth. The Industrial Revolution 4.0 has a positive impact that can help human activities, which were originally carried out traditionally, can be carried out by utilizing technology. During the pandemic that we have experienced, there is no reason not to be productive as long as we stay at home, with this technology it can help with daily life activities. One form of technology utilization carried out by the Faletehan University Management Study Program is to hold community service in the field of entrepreneurship with the theme Digitalization Business Development Program to Increase Family Income. spare time in business practices in various businesses to be able to become a business person at least for the welfare of his family. Even this activity is based on the problem that arises from the lack of a ratio between the number of entrepreneurs and the population of its citizens because the requirement for a developed country is to have a ratio of 14%. According to Law no. 12 of 2012 Higher Education is an institution that has an important role in creating creative and innovative resources so that they can produce various works or products that can encourage the growth of the Indonesian economy. Therefore, higher education has the potential to create entrepreneurs who can utilize technology or are called technopreneurs. The objectives of this PKM activity for Posyandu Mekarsari kramatwatu mothers are 1). Society is expected to maximize the use of technology as a means of business 2). Producing New Products 3). Adding to the Economy in the Family 4). Confident and skilled.